Willingness to accept compensation of seaweed cultivators to shift from mariculture to ecotourism related businesses for conservation of marine resources in Tun Sakaran Marine Park: the preliminary study - Mohd Nasir, Nur Afifah; Samdin, Zaiton (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
Sabah is the sole producer of seaweeds in Malaysia with most of total production is cultivated off Semporna coasts (Sade, Ali, & Mohd., 2006). Tun Sakaran Marine Park (TSMP), located in Semporna Island is unique because there are human settlements inside and seaweed cultivation can be found within Selakan-Sebangkat areas under Sabah Park provision. Somehow, lack of knowledge in practising environmental-friendly farming way and destructive fishing practices like usage of dangerous explosive materials resulting to corals destruction that became the attraction for snorkelling and diving activities. TSMP also is the most visited island by tourists after Sipadan and Mabul Islands. Therefore, this study will investigate the potential of adopting Payments for Ecosystem Services (PES) scheme for marine ecosystem conservation in TSMP by implementing microeconomic concept of willingness to accept (WTA) to the seaweed cultivators. The alternative is by giving them compensation to reduce their production by 25%, 50%, 75% or fully shift from seaweed mariculture to ecotourism related businesses such as tour guides, boatmen and so on. The respondents are the seaweed cultivators in both Selakan and Sebangkat areas in which Choice Experiment (CE) based questionnaire is employed to investigate preference of shifting and compensation value. It is expected that the finding of this paper is able to reflect the suitability of WTA implementation for marine conservation in TSMP.